Attitude of Secondary School Teachers towards Students living with HIV/AIDS in Sokoto South and North Metropolis Nigeria - Nofiu, Oluwatobi Daniel; Gana, Mohammed Kaka; Abdulkadir, Mariam Audu; Kamar, Abdulkadir (NIU Journal of Humanities, 2023)
The research determined teachers' attitude towards people/students living with Human Immunodeficiency Syndrome Arid Acquired Immune Deficiency Syndrome HIV/ AIDS and described the results from the selected sample of 1200 participants; using simple random sampling. The study employed quantitative research design, utilizing a single blinded Randomized Control Trial conducted between February to July 2022 in Sokoto South and Sokoto North local Government Area of Sokoto State, Nigeria. Data on socio-demographic characteristics of the respondents and HIV/AIDS related attitude were collected using a validated questionnaire. Data was analyzed using Analisis of Variance (ANOVA) and simple percentages. at P< 0.05. The results revealed that analysis revealed that, the mean baseline scores for Teachers' Attitude between intervention and control groups was low (mean = 42.90; 1.88), 64.31 (5.35), 60.36 (2.49); F (2, 2360.382), P < 0.001). No significant difference was found between the groups as regards their attitude of HIV/AIDS. Mean baseline HIV/AIDS attitude of the respondents did not differ and poor attitude was reported in intervention and control groups respectively. Therefore, there is need for HIV/AIDS education intervention to improve the attitude of some secondary school teachers. Keywords: HIV/AIDS, attitude, teachers, students.